Biological relevance of ZNF224 expression in chronic lymphocytic leukemia and its implication IN NF-kB pathway regulation - Catapano, Rosa; Sepe, Leandra; Toscano, Elvira; Paolella, Giovanni; Chiurazzi, Federico; Barbato, Serafina Patrizia; Bruzzese, Dario; Arianna, Rosa; Grosso, Michela; Romano, Simona; Romano, Maria Fiammetta; Costanzo, Paola; et al. (Frontiers in Molecular Biosciences, 2022)
Chronic lymphocytic leukemia (CLL) is a heterogeneous disease, whose presentation and clinical course are highly variable. Identification of novel prognostic factors may contribute to improving the CLL classification and providing indications for treatment options. The zinc finger protein ZNF224 plays a key role in cell transformation, through the control of apoptotic and survival pathways. In this study, we evaluated the potential application of ZNF224 as a novel marker of CLL progression and therapy responsiveness. To this aim, we analyzed ZNF224 expression levels in B lymphocytes from CLL patients at different stages of the disease and in patients showing different treatment outcomes. The expression of ZNF224 was significantly increased in disease progression and dramatically decreased in patients in complete remission after chemotherapy. Gene expression correlation analysis performed on datasets of CLL patients revealed that ZNF224 expression was well correlated with that of some prognostic and predictive markers. Moreover, bioinformatic analysis coupled ZNF224 to NF-kB pathway, and experimental data demonstrated that RNA interference of ZNF224 reduced activity of the NF-kB survival pathway in CLL cells. Consistently with a pro-survival role, ZNF224 knockdown raised spontaneous and drug-induced apoptosis and inhibited the proliferation of peripheral blood mononuclear cells from CLL patients. Our findings provide evidence for the involvement of ZNF224 in the survival of CLL cells via NF-kB pathway modulation, and also suggest ZNF224 as a prognostic and predictive molecular marker of CLL disease.